The Effects of Using Social Media and Product Innovation in Improving Marketing Performance - Asniwati, Asniwati; Latief, Fitriani; Heriyanti, Mufti (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
The aim of this research is to partially analyze the influence of social media use and product innovation on marketing performance. The analytical approach used in this research is descriptive quantitative. The population in this research is all Big Bananas customers in the city of Makassar, the number of which is unknown.The type of non-probability sampling method used is judgmental sampling using the Rao Purba formula for sampling.So the total sample for this research is 96 Big Bananas consumers. The data analysis approach used in this research is multiple regression analysis. The research results found that partially the use of social media and product innovation had a significant effect on marketing performance